IDENTIFICATION OF MISTAKES IN CONCEPTS, PRINCIPLES AND MATHEMATICAL OPERATIONS OF SECONDARY SCHOOL STUDENTS IN ALGEBRAIC PROBLEM IN VIEW OF THE VISUALIZER LEARNING STYLE - Nuri Rahmiaty (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2024)
One of the factors causing the failure to achieve the goals of students' mathematics learning is the discovery of many errors in the results of student work in solving problems, student errors in working on questions can be one of the teacher's instructions to find out the extent to which students master the material. The purpose of this study was to determine student errors in solving algebra problems at SMP Negeri 1 Simpang Tiga Aceh Besar. This study used a qualitative approach with the research subject consisting of three students who were taken based on the number of errors made in solving algebraic operations and communication skills. Data were collected through tests and interviews which were then analyzed by reducing data, presenting data, and drawing conclusions with the validity of the data by triangulation of sources. The results showed that there were several student errors, such as (1) conceptual errors, student errors in understanding questions and student errors in making mathematical sentences, factors causing errors due to students not understanding the questions given; (2) principle errors, student errors in operating the properties that exist in algebraic operations and wrong in drawing conclusions and determining the final answer, factors that cause errors because students write without being careful in drawing conclusions and determining final answers and students do not understand the properties properties that exist in algebraic operations; and (3) operational errors, errors made by students in using operations or calculations, both addition, subtraction, multiplication and division, factors that cause errors because students are not careful and do not understand the questions given so they do not make good solutions. Keywords: Analysis, Student Error, Algebra Problems.